Global Stability of Harmful Phytoplankton and Herbivorous Zooplankton with Holling Type IV Functional Response - Shalan, Rehab Noori; Aljaf, Dina; Ibrahim, Hiba Abdullah (Al-Nahrain Journal of Science, 2018)
In this paper harmful phytoplankton and herbivorous zooplankton model with Hollimg type IV functional response is proposed and analyzed. The local stability analysis of the system is carried out. The global dynamics of the system is investigated with the help of the Lyapunov function. Finally, the analytical obtained results are supported with numerical simulation.